Digital Diplomacy and Nation Branding of Indonesian Ecotourism: An Analysis of the Role of Environmental Education in the YOLO Program on the CubMu Platform as an Instrument of Public Diplomacy - Agriana, Nur Sabriani; Dermawan, Windy; Permana, Niksi Riyani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study analyzes the potential of Indonesia’s ecotourism as a soft power instrument in digital public diplomacy through the CubMu platform and the YOLO (You Only Live Once) program. The main objective of this research is to examine how environmental narratives are constructed and disseminated through digital storytelling as part of Indonesia’s efforts to build a sustainable global image. Using a descriptive qualitative approach based on literature review and digital discourse analysis, this study finds that CubMu’s communication practices contribute to framing ecotourism as a reflection of Indonesia’s commitment to global environmental issues, although its dissemination remains predominantly regional. The YOLO program demonstrates potential in reaching the global youth audience through emotionally engaging and visually appealing narratives; however, its effectiveness is limited by risks of over-commercialization and digital infrastructure gaps in rural areas. The study concludes that integrating ecotourism and digital diplomacy can strengthen Indonesia’s position as a proactive actor in environmental diplomacy while opening new avenues for sustainability-oriented soft power.